The Effect of Amino Acids Lysine and Methionine on the Carcass of Native Chickens - I Nengah Andri Bayu Dita dita; Ni Ketut Sri Rukmini; Ni Made Yudiastari (SEAS (Sustainable Environment Agricultural Science), 2020)
This study aims to determine the effect of 1% lysine, 0.5% methionine and the combination of lysine and methionine (1% + 0.5%) in the ration on the weight gain of carcass parts of native chickens. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 3 replications, while the treatments were R0 (control) native chickens that were not given additional lysine and methionine, R1 native chickens were given feed containing lysine 1 %, R2 of free-range chickens given feed containing 0.5% methionine, R3 of native chickens given feed containing lysine and methionine (1% + 0.5%). The parameters observed were the weight gain in the chest, thighs, wings, and back. The data obtained were analyzed by analysis of variance. The results showed that the provision of rations which were added with the combination of amino acids lysine and methionine had a very significant effect (P> 0.01) on the weight gain of the carcass, thighs and backs of native chickens aged 10 weeks. Based on the results of this study it can be concluded that the combination of the amino acids lysine and methionine in the ration gave the best effect on the weight gain of carcass parts of native chicken aged 10 weeks. Based on the results of the study, it is suggested to add the combination of lysine (1%) and methionine (0.5%) in the native chicken ration. Keywords: native chickens, carcass weight, lysine, methionine